2014
DOI: 10.1111/ajt.12630
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoalveolar Lavage Cell Immunophenotyping Facilitates Diagnosis of Lung Allograft Rejection

Abstract: Supplementary methods to identify acute rejection and to distinguish rejection from infection may improve clinical outcomes for lung allograft recipients. We hypothesized that distinct bronchoalveolar lavage (BAL) cell profiles are associated with rejection and infection. We retrospectively compared 2,939 BAL cell counts and immunophenotypes against concomitantly obtained transbronchial biopsies and microbiologic studies. We randomly assigned 317 subjects to a derivation or validation cohort. BAL samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
69
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(77 citation statements)
references
References 38 publications
1
69
0
1
Order By: Relevance
“…23 Chronic lung allograft dysfunction (CLAD) was defined according to established criteria as an unresolving 20% decline in FEV 1 or FVC lasting over 30 days 24 and determined from clinical records as previously described. 25,26 CLAD-free survival was quantified as years of freedom from CLAD or death.…”
Section: Clinical Data and Outcomesmentioning
confidence: 99%
“…23 Chronic lung allograft dysfunction (CLAD) was defined according to established criteria as an unresolving 20% decline in FEV 1 or FVC lasting over 30 days 24 and determined from clinical records as previously described. 25,26 CLAD-free survival was quantified as years of freedom from CLAD or death.…”
Section: Clinical Data and Outcomesmentioning
confidence: 99%
“…A greater concentration of NK cells in bronchoalveolar lavage (BAL) fluid has been observed during acute cellular rejection, even though the NK cell percentage of total BAL lymphocytes decreased 43. In subjects with CLAD, NK cell peripheral blood frequencies were decreased, but these NK cells had a more activated phenotype 43. CLAD subjects also have higher numbers of NK cells in allograft transbronchial biopsy specimens 44.…”
Section: Introductionmentioning
confidence: 99%
“…However, a study of 27 subjects found no correlation between PBMC Treg frequency and risk of acute lung allograft rejection 9 . Increased Treg frequencies in bronchoalveolar lavage (BAL) fluid and transbronchial biopsy tissue have been associated with acute cellular rejection 10,11 and increased regulatory T cell frequencies have been found in endomyocardial biopsies prior to the development of acute cardiac allograft rejection 12 . Further, studies to date have evaluated total rather than donor-reactive subsets of Treg, leaving the association between acute rejection and systemic donor-reactive Treg undefined.…”
Section: Introductionmentioning
confidence: 99%